THE INFLUENCE OF MACROECONOMIC VARIABLES ON THE JAKARTA ISLAMIC INDEX (JII): AN ANALYSIS FROM 2010 TO 2023 - Dian Prehatin; Slamet Haryono (Universitas Airlangga, 2024)
Introduction: Sharia investment activities become one of the most promising economic activities. This is proven from the resilience of sharia capital market activities, which have remained strong despite the challenges of the Covid-19 pandemic. This research examine the influence of macroeconomic variables on the Jakarta Islamic Index (JII). Method: This research used a quantitative approach with time series data for the period of January 2010 to December 2023. Specifically, the Vector Error Correction Model (VECM) method was employed to examine both the long-term and short-term effects, as well as the shocks in macroeconomic variables on Jakarta Islamic Index (JII). Results: This study indicate that in the long term, the exchange rate, IHSG and WGP variables have a significant positive impact on JII, while the inflation variable has a significant negative impact. Conversely, the WGP variable shows an insignificant negative impact on stock movements rates within JII. In the short term, however, the variables of inflation, exchange rate, IHSG, COP (Crude Oil Prices) and WGP do not have any impact on the movement of shares listed on JII. Conclusions and Suggestions: The findings of this research encourage investors to pay more attention to the movement of macroeconomic rate variables and information from companies related to financial reports before making a decision to invest their capital. The inflation, exchange rate, and IHSG variables can be utilized as references in decision making because better movement of the IHSG and exchange rate and stable inflation are able to provide optimal returns for investors.